2020
DOI: 10.1063/5.0014829
|View full text |Cite
|
Sign up to set email alerts
|

Suboxide interface induced digital-to-analog switching transformation in all Ti-based memristor devices

Abstract: Oxidation of TiN is a diffusion-limited process due to the high stability of the TiN metallic state at the TiN/TiO2 junction. Hence, the TiN/TiO2/TiN device being the inability to form a suitable interfacial layer results in the exhibition of abrupt current (conductance) rise and fall during the set (potentiation) and reset (depression) processes, respectively. Interfacial engineering by depositing Ti film served as the oxygen gettering material on top of the TiO2 layer induces a spontaneous reaction to form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It is also can be regarded that the BFO layer can act as an oxygen reservoir to promote gradual oxidation and reduction of the Hf CFs during the set and reset processes. [ 50 ] Therefore, it is reasonable to believe that the BFO inserting layer can lead to the linearity improvement of the LTP and LTD.…”
Section: Resultsmentioning
confidence: 99%
“…It is also can be regarded that the BFO layer can act as an oxygen reservoir to promote gradual oxidation and reduction of the Hf CFs during the set and reset processes. [ 50 ] Therefore, it is reasonable to believe that the BFO inserting layer can lead to the linearity improvement of the LTP and LTD.…”
Section: Resultsmentioning
confidence: 99%
“…interfacial engineering techniques such as doping of impurity, [23][24][25] multiple temperature annealing and insertion of barrier layer or modulation layer were applied to confine the filament area in order to achieve stable MLC capability. [26][27][28] Moreover, mostly memristors tend to degrade their storage capabilities under humid and varying temperature environment. Considerable amount of research is inclined toward this to mitigate these issues and make devices favorable for wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Henceforth, careful engineering in the formation and rupture of conductive filament/bridge to achieve gradual switching is required. 14 Several techniques are recently reported that digital switching can be transformed into analog switching in memristor devices either by using annealing processes, different doping concentrations, or different top electrodes. [15][16][17] In this work, we demonstrate that such transformation could also be achieved by the employment of a barrier layer(BL) in TaOxbased CBRAM devices.…”
mentioning
confidence: 99%